Beyond power struggles: a multilevel perspective on incongruences at the interface of practice, knowledge, and identity in radical organizational change - Kump, Barbara (2019)
Previous approaches to describing challenges inherent in radical organizational change have mainly focused on power struggles. A complementary but less researched view proposes that many problems occur because radical change causes certain incongruences within an organization. In line with the latter perspective, this article suggests that radical change leads to incongruences between (3z(Bwhat they do(3y (B(practice), (3z(Bwhat they know(3y (B(knowledge), and (3z(Bwho they are(3y (B(identity) as an organization; to achieve the change, these incongruences need to be accommodated by the organization$1 (Bs individual members. The article takes a multilevel perspective and describes how in radical change organizational goals may interfere with individual characteristics at the intersections of practice, knowledge, and identity. This enables a fine-grained analysis of reasons why radical change efforts may fail, beyond power struggles. The model is concrete enough to help change managers foresee many practical problems, such as member disidentification, routine breakdowns, or knowledge gaps. - Reproduced.s
Keywords: Organisational change